2014
DOI: 10.1186/1471-230x-14-154
|View full text |Cite
|
Sign up to set email alerts
|

Association between ERCC1 and TS mRNA levels and disease free survival in colorectal cancer patients receiving oxaliplatin and fluorouracil (5-FU) adjuvant chemotherapy

Abstract: BackgroundAim was to explore the association of ERCC1 and TS mRNA levels with the disease free survival (DFS) in Chinese colorectal cancer (CRC) patients receiving oxaliplatin and 5-FU based adjuvant chemotherapy.MethodsTotal 112 Chinese stage II-III CRC patients were respectively treated by four different chemotherapy regimens after curative operation. The TS and ERCC1 mRNA levels in primary tumor were measured by real-time RT-PCR. Kaplan–Meier curves and log-rank tests were used for DFS analysis. The Cox pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
(29 reference statements)
2
6
0
Order By: Relevance
“…The present study in line with other authors [9], has not confirmed that overexpression of TYMS protein or transcript predicts poor outcome in colorectal cancer patients [7,8]. Similarly, the results of studies indicating potential prognostic role of DPYD [10,11] or TYMP [12] expression for survival of colorectal cancer patients after 5-FU-treatment were not replicated.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The present study in line with other authors [9], has not confirmed that overexpression of TYMS protein or transcript predicts poor outcome in colorectal cancer patients [7,8]. Similarly, the results of studies indicating potential prognostic role of DPYD [10,11] or TYMP [12] expression for survival of colorectal cancer patients after 5-FU-treatment were not replicated.…”
Section: Discussionsupporting
confidence: 58%
“…Recent studies have shown that overexpression of TYMS transcript predicts poor outcome in colorectal cancer patients [7,8]. However, another contemporary study has not confirmed these observations as intratumoral TYMS transcript level was not predictive in patients with colorectal cancer of stage II and III [9].…”
Section: Introductionmentioning
confidence: 99%
“…They determined that the mRNA expression level of ERCC1 was not significantly associated with the DFS in Chinese patients with stage II to III colorectal cancer who received 5-FU and oxaliplatin-based adjuvant chemotherapy; neither did they find a significant association between DFS and thymidylate synthase. On the other hand, another study of patients with stage III colon cancer who received oxaliplatin-based adjuvant chemotherapy reported that the 5-year DFS was significantly higher in patients with ERCC1-negative tumors (72%) than in patients with ERCC1-positive tumors (54%) (hazard ratio, 1.98; 95% confidence interval, 1.19-3.31; P = 0.009) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…5-Fluorouracil (5-FU) is a cell cycle specific drug that can inhibit thymidylate synthase activity in tumor cells in vivo by blocking the biosynthesis of deoxythymidine from deoxyuridine and eventually inhibiting DNA synthesis [1,2]. Furthermore, it also can prevent uracil and orotic acid uptake into RNA to inhibit the effects of RNA, and thus interferes with the biosynthesis of RNA, DNA, and proteins [3,4].…”
Section: Introductionmentioning
confidence: 99%